Evaluation of students' conceptual understanding of fluid mechanics course through diagnostic assessment in odl platform - Mokhtar, Hamizah; Abdul Rahman, Nurul Aishah; Muhamad, Noor Safwan; Ismail, Muhammad Isha (GADING Journal for the Social Sciences, 2022)
The fluid mechanics concept is widely applied in current technology and our daily lives, requiring students to understand the significance of this concept. The issues arising for the Civil Engineering Diploma students who have difficulties understanding physics concepts in Physics course (PHY145) at semester 1 and lead to more complex concepts in fluid mechanics course (ECW231) at semester 3 through the Open and Distance Learning (ODL) platform. Physics course act as pre-requisite to enroll in fluid mechanics course. Present research investigates students' conceptual understanding of physics using a diagnostic assessment. The diagnostic assessment is an entering test for fluid mechanic's course. The result obtained from the distributed diagnostic assessment question is analyzed to achieve this objective. A survey also was conducted to determine the necessity for diagnostic assessment in Fluid Mechanics course. The major findings of the study are 100% lecturers agreed that diagnostic tests could help them detecting student weaknesses at early stage. Hence, teaching-learning strategies and approaches must be adjusted according to students' learning needs.